PENGARUH KUALITAS PELAYANAN DAN TARIF TERHADAP LOYALITAS PELANGGAN BUS DAMRI KOTA SEMARANG ( Studi pada penumpang bus DAMRI rute Ngaliyan – Pucang Gading Semarang ) - Setyaji Herlambang; Agus Hidayat; Sari Listyorini (Universitas Diponegoro, 2013)
Perum DAMRI UABK Semarang is a company engaged in the field of public transport bus services in the city of Semarang .Competition intensifies city transportation makes perum DAMRI seek to various strategies to retain customers . As a company engaged in the field of services , Perum DAMRI must provide good service to its customers to use your services in order to remain loyal , good service offset by the rates in accordance with what is provided by Perum DAMRI to customers . Type of explanatory research studies using the method of data collection using interviews and data collection devices using a questionnaire with a sample of 100 respondents who waited at bus stops 4 bus routes impassable DAMRI Ngaliyan – Pucang Gading using purposive sampling method . Based on a statistical calculation known that the positive effect of service quality on customer loyalty of 45.5 % if the service quality is increased it will increase customer loyalty , while the rate has a positive effect on customer loyalty at 43.0% , if the rates is increased it will increase customer loyalty but emotion balanced with appropriate facilities . Together - the same quality of service and influence on customer loyalty rates of 50.8 % . While the remaining 49.2 % is explained by other variables that are not observed . Suggestion for the company , the company maintains quality of service that has been given to improve the timeliness of the arrival of the bus is still late sometimes , repair damaged facilities began , and giving clearer information rates for long distance and short distance .